Wells Cathedral
The pointed vaults of Wells Cathedral nave are truly Gothic. Both the diagonal ribs and the cross ribs are pointed, and the high vault is completely integrated with the nave design. Flying buttresses, concealed within the triforium stage, accept the thrusts.